Clinicopathological, radiographic, and oncogenic features of primary pulmonary enteric adenocarcinoma in comparison with invasive adenocarcinoma in resection specimens. Issue 39 (September 2017) - Zhao, Long; Huang, Shanshan; Liu, Jinjun; Zhao, Juan; Li, Qiang; Wang, Huo-Qiang
Abstract : Abstract: Primary pulmonary enteric adenocarcinoma (PEAC) is a rare subtype of primary lung adenocarcinoma. However, it is not known whether there are any distinctive clinical or molecular features. PEACs were retrospectively identified in 28 patients from July 2014 to June 2016. We compared the clinicopathological, radiographic, and oncogenic characteristics of PEAC and primary pulmonary invasive adenocarcinoma (IAC). A total of 28 PEAC patients and 92 IAC patients were compared. PEAC occurred more frequently in males ( P  = .008), in older patients ( P  = .041), in those with larger lesions ( P  = .001), and in those in a more advanced stage ( P  = .011). Radiologically, PEAC patients had larger lesions ( P  = .025) and more solid ( P  = .006); however, there were no statistically significant differences in lobulation, spiculation, pleural indentation, pleural effusion, and lymphadenopathy between PEAC and IAC. PEAC had higher values of carcinoembryonic antigen ( P  = .008) and carbohydrate antigen 19-9 ( P  < .001) than IAC. PEAC had a higher incidence (40% vs 63%, P  < .001) of Kristen rat sarcoma viral oncogene homolog ( KRAS ) mutations and a lower incidence (10.71% vs 3.3%, P  < .001) of epidermal growth factor receptor ( EGFR ) mutations. Villin may be a useful marker in the differential diagnosis of PEAC. KRAS mutations occurred more frequently in PEACs, which are cytokeratin 7-negative ( P  = .032). EGFR mutation rates were higher in PEACs, which are cytokeratin 20- and caudal type homeobox transcription factor 2-negative ( P  = .041). PEAC is a rare and heterogeneous nonsmall-cell lung cancer subgroup with distinctive clinicopathological, radiographic, and molecular features. These results need to be further confirmed in future studies.